BDY532: Global Climate Change / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2023)
This introductory course on climate change presents Earth’s climate system and explores the science and politics of global climate change. We will cover the topics from global climate change texts books, the 2007 IPCC report, various advanced climate texts, and current journal literature. This 14 weeks’ course consists of 10 lessons. Course topics include the greenhouse effect, ocean circulation, the science and politics of climate change and climate change impacts on Malaysia.